Complement pathway: Risk molecular pattern of cardiovascular diseases in patients with diabetic nephropathy - Liu, JunFei; Qian, XiaoPing; Wang, TaoXia; Liu, XiaoLi; Liu, WeiGang; Wang, LiJie; Zhang, HuiFang; Han, Li; Li, GuiYing; Yu, XiaoJuan (Journal of Medical Biochemistry, 2025)
Background: Diabetic nephropathy (DN) commonly occurs as a microvascular complication in individuals with diabetes mellitus (DM). The progression of renal dysfunction in DN patients leads to a marked rise in the risk of cardiovascular disease (CVD). At present, the effective treatment of DN and CVD necessitates the identification and management of their risk factors.Methods: Patients diagnosed with DN from October 2022 to October 2023 were selected for cross-sectional study and divided into DN group (n = 58) and DN/CVD group (n = 40). Clinical data were collected for univariate analysis, and independent variables that were statistically significant were analyzed with multivariate Logistic regression to identify independent influencing factors of CVD in DN patients. A regression model was developed to examine the non-linear relationship between C1q, UA, CRP, and the risk of CVD. Receiver operating characteristic (ROC) curve was used to analyze the predictive efficacy of the indicators.Results: UA and C1q, when elevated, were independent factors increasing the risk of CVD. A linear relationship existed between UA and C1q and the risk of CVD in DN patients, showing a correlation. C1q showed better predictive performance.Conclusion: As UA and C1q levels rise, the risk of CVD in the DN group significantly increases. In DN patients, UA and C1q are associated with CVD development and progression, offering some supportive evaluation value for the patient's condition.
Keywords: Complement pathway; Diabetic nephropathy; Cardiovascular events; Complications